2020
DOI: 10.1080/14779072.2020.1826308
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme inhibitors and angiotensin II receptor blockers and outcomes in patients with COVID-19: a systematic review and meta-analysis

Abstract: Background: The use of angiotensin-converting enzyme inhibitors (ACEI) and angiotensin II receptor blockers (ARB) in patients with coronavirus disease 2019 (COVID-19) given their interaction with the angiotensin-converting enzyme-2 (ACE-2) receptor remains controversial.. Objective: To investigate the impact of ACEI/ARB on COVID-19 disease severity and mortality through a systematic review and meta-analysis. Methods: We searched PubMed and CINAHL databases as well as pre-print servers for studies investigating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 33 publications
(56 reference statements)
1
34
0
1
Order By: Relevance
“…For example, because of SARS-CoV-2's interactions with angiotensin converting enzyme receptors, there have been a number of studies on how angiotensin converting enzyme inhibitor medications may impact the risk of a mild COVID-19 case progressing to more serious illness among patients who were taking these drugs for their cardiovascular effects when they were diagnosed with COVID-19. [15][16][17] There has also been considerable interest regarding whether hydroxychloroquine or other drugs could be prescribed as early treatment to prevent serious disease among patients testing positive for COVID-19. When assessing study validity of the treatment effectiveness in this context it helps to differentiate between studies of treatments used for conditions other than COVID in patients who then happen to be infected vs. medications that are specifically prescribed after an infection in the hope to alleviate the presentation of COVID.…”
Section: Medication Effectiveness In Ambulatory Care Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, because of SARS-CoV-2's interactions with angiotensin converting enzyme receptors, there have been a number of studies on how angiotensin converting enzyme inhibitor medications may impact the risk of a mild COVID-19 case progressing to more serious illness among patients who were taking these drugs for their cardiovascular effects when they were diagnosed with COVID-19. [15][16][17] There has also been considerable interest regarding whether hydroxychloroquine or other drugs could be prescribed as early treatment to prevent serious disease among patients testing positive for COVID-19. When assessing study validity of the treatment effectiveness in this context it helps to differentiate between studies of treatments used for conditions other than COVID in patients who then happen to be infected vs. medications that are specifically prescribed after an infection in the hope to alleviate the presentation of COVID.…”
Section: Medication Effectiveness In Ambulatory Care Settingsmentioning
confidence: 99%
“…Much of the work on outpatient medications used for COVID‐19 has focused on how existing medications may lower disease severity among infected patients. For example, because of SARS‐CoV‐2’s interactions with angiotensin converting enzyme receptors, there have been a number of studies on how angiotensin converting enzyme inhibitor medications may impact the risk of a mild COVID‐19 case progressing to more serious illness among patients who were taking these drugs for their cardiovascular effects when they were diagnosed with COVID‐19 15–17 . There has also been considerable interest regarding whether hydroxychloroquine or other drugs could be prescribed as early treatment to prevent serious disease among patients testing positive for COVID‐19.…”
Section: Medication Effectiveness In Ambulatory Care Settingsmentioning
confidence: 99%
“…Several meta-analyses have concluded that antecedent ACEi/ARB prescription did not predispose to worsened outcomes in COVID-19. [6][7][8] Others concluded that prior ACEi/ARB use reduced the risk of mortality and ICU admission, and decreased length of stay. [9][10][11][12][13][14] There is theoretical basis for both deleterious and protective effects of these agents in SARS-CoV-2 infection.…”
Section: Comparisons With the Literaturementioning
confidence: 99%
“…Broadly these suggest that antecedent ACEi/ARB therapy is not associated with worsened outcomes in COVID-19, and that their use might confer certain protective benefits. [6][7][8][9][10][11][12][13][14] The impact of ACEi/ARB provision during acute COVID-19 illness has been inadequately examined. To date few studies have attempted to address this question.…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время имеются неоспоримые доказательства того, что отказ от планового приема ингибиторов ангиготензин-превращающего фермента (иАПФ) или блокаторов рецепторов к ангиотензину (БРА) существенно увеличивает риск сердечно-сосудистых катастроф у пациентов с новой коронавирусной инфекцией, вызванной вирусом SARS-CoV-2 [8]. Применение этих лекарственных препаратов способствует уменьшению выраженности фиброза миокарда, улучшению функции эндотелия, активации медиаторов окислительного стресса и уменьшению воспаления, что обеспечивает кардиопротективные эффекты при COVID-19.…”
Section: антигипертензивная терапия в лечении постковидного синдромаunclassified